2017
DOI: 10.1017/s2040174417000113
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical artery histomorphometry: a link between the intrauterine environment and kidney development

Abstract: Prematurity is a risk factor for hypertension, vascular stiffness, nephron deficit and adult onset cardiorenal disease. The vascular tree and kidneys share morphogenic drivers that promote maturation in utero before 36 weeks of gestation. Vascular elastin accrual terminates after birth leaving collagen to promote vascular stiffness. Our objective was to determine if the histomorphometry of the umbilical artery, an extension of the aorta, parallels nephron mass across gestational age groups. From a cohort of 54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Thus, the in utero environment in turn influences the health of the child (C). Specific to this review, blood flow within the umbilical cord increases with gestational age and rates of preterm birth and low birth weight are 50 -100% higher in black versus white infants (6,20). These birth outcomes can occur without maternal clinical symptoms and may not be reported by commercial human umbilical vein endothelial cell (HUVEC) vendors.…”
Section: A B Cmentioning
confidence: 99%
“…Thus, the in utero environment in turn influences the health of the child (C). Specific to this review, blood flow within the umbilical cord increases with gestational age and rates of preterm birth and low birth weight are 50 -100% higher in black versus white infants (6,20). These birth outcomes can occur without maternal clinical symptoms and may not be reported by commercial human umbilical vein endothelial cell (HUVEC) vendors.…”
Section: A B Cmentioning
confidence: 99%
“…Concerning the tunica adventitia, it is composed of fibrous and elastic connective tissue with variable amounts of collagen and elastic fibers. In the case of the tunica adventitia of the vein, it is composed of less dense connective tissue [30].…”
Section: Vessels Of Hucmentioning
confidence: 99%
“…Maternal vascular malperfusion, frequently associated with small for gestational age preterm infants, results in placental aging and may affect Klotho production by the placenta; cord blood Klotho levels were measured in a case-control study and, compared to normal controls, were found to be significantly lower in infants born prematurely and with placental vascular findings consistent with accelerated aging that contributed to intrauterine growth retardation [137]. Prematurity and other perinatal exposures are associated with increased risks of cardiometabolic risk factors, CKD, HTN, and CV disease that are likely due to multiple intrauterine and extrauterine factors that may alter kidney, cardiac, and vascular structure and function [138,139]. These alterations affecting perinatal programming may alter the RAAS, with lower Ang-(1-7) and a higher Ang II/ Ang-(1-7) ratio that may persist and contribute to higher BPs later in life, as documented in adolescents with a history of premature birth [140].…”
Section: Klotho Reactivation and Exogenous Administrationmentioning
confidence: 99%